2021
DOI: 10.1016/j.jbusres.2021.03.059
|View full text |Cite
|
Sign up to set email alerts
|

Bundling and exporting: Evidence from German SMEs

Abstract: This paper studies the effect of bundling products and services on the export performance of firms. Using a unique sample, we document several facts about German small and medium enterprises (SMEs). First, bundling is a relatively rare activity, which is unevenly spread across sectors. Second, SMEs that bundle products and services are more productive than those selling products and services separately. Third, these firms tend to be more internationally oriented. While most of the existing literature focuses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 95 publications
0
13
0
Order By: Relevance
“…Previous studies had dealt with the effects of servitization and internationalization on the performance of an enterprise in a fragmented manner (Cano-Kollmann et al. , 2016; Aquilante and Vendrell-Herrero, 2021). However, the present study extended the idea and applied it to investigate how manufacturing SMEs could improve their performances by internationalizing their businesses by developing a process of servitization, thus adding value to the body of literature (Shleha et al ., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had dealt with the effects of servitization and internationalization on the performance of an enterprise in a fragmented manner (Cano-Kollmann et al. , 2016; Aquilante and Vendrell-Herrero, 2021). However, the present study extended the idea and applied it to investigate how manufacturing SMEs could improve their performances by internationalizing their businesses by developing a process of servitization, thus adding value to the body of literature (Shleha et al ., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Fernandes and Winters (2021) studied the influence of political factors (Brexit referendum) as a quasi-natural experiment to study the impact of exchange rate shocks and uncertainty on the prices and volumes of export traffic for Portuguese exporters. One should mention that examining the problems of the impact of certain factors on exports, the researchers concluded that the combination of goods and services is closely linked to the level of export intensity (Aquilante & Vendrell-Herrero, 2021). Based on a study of six global management indicators as explanatory factors for exports and their components, Bah et al (2021) have found that political stability, the rule of law, control of corruption, voice, and accountability have a positive effect on export performance.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…On the contrary, the use of a questionnaire survey is based on a number of different researches in various areas of economic research (Aquilante & Vendrell-Herrero, 2021), (Du et al, 2021) or (Casper Ferm & Thaichon, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%